DEVELOPMENT OF AN INTERACTIVE WEBSITE WITH DIDACTIC GAMES TO ENHANCE VOCABULARY IN YOUNG STUDENTS WITH INTELLECTUAL DISABILITIES - Anna Bober; Yuriy Kosenko; Olena Korol (Інформаційні технології і засоби навчання)
The article investigates the development of a website that includes interactive didactic games designed to improve the vocabulary of primary schoolchildren with intellectual disabilities. It describes the importance of developing vocabulary in children with intellectual disabilities and shows how the game approach can be an effective tool for teaching and developing speech in this category of children. The process of developing a website with didactic games is considered, which includes the selection of appropriate software, interface design, development of interactive tasks and games, as well as testing and improvement of the website. In particular, the article discusses methods and approaches to creating games aimed at developing lexical skills, expanding vocabulary and improving communication skills in children with intellectual disabilities. The advantages of using interactive didactic games in the educational process of junior schoolchildren with intellectual disabilities are highlighted. They stimulate children's interest in learning words and expanding their vocabulary, develop cognitive and speech skills, improve memory and concentration, and increase motivation and enjoyment of learning. A game-based approach can keep children interested, motivated, and effective, helping them to develop their language skills and achieve greater academic success. The website was created on the wix platform. The collection of didactic games was developed on the LearningApps platform. There are various types of tasks, for example quizzes, puzzles, crosswords, matching exercises, etc. Images for didactic games were generated by playground.ai artificial intelligence, which opens up new opportunities for creating visually appealing games and tasks. The importance of developing website with interactive didactic games for the development of vocabulary of younger students with intellectual disabilities is emphasized, they can become an effective tool for teaching and developing speech in children of this category, contributing to their success in learning and overall development.